The eastern Pacific species of Salmoneus Holthuis, 1955, with description of a remarkable new species from Las Perlas Archipelago, Panama (Malacostraca: Decapoda: Alpheidae) - Anker, Arthur (Zootaxa, 2019)
The present study deals with five species of the alpheid shrimp genus Salmoneus Holthuis, 1955 from the tropical eastern Pacific. One of them is new to science and is described as Salmoneus tiburon sp. nov. The new species is presently known only from the Las Perlas Archipelago in Panama and can be distinguished from all other congeners by the dentition on the cutting edges of the major chela, with some dactylar teeth reminiscent of shark teeth. It is also one of the largest species of the genus, with the carapace length of both type specimens surpassing 8.0 mm. Salmoneus serratidigitus (Coutière, 1897), a species with an ample distribution across the Indo-Pacific, is recorded for the first time from the Pacific coast of Panama and is confirmed from Colombia. Salmoneus malagensis Anker & Lazarus, 2015, previously known only from Bahía Málaga in Colombia, is recorded from Panama’s Azuero Peninsula. The remaining two species, S. excavatus Anker, 2011 and S. alvarezi Anker & Lazarus, 2015, are recorded regionally from Las Perlas Archipelago in Panama and Playa Tarcoles in Costa Rica, both for the first time since their original descriptions. An identification key to the five currently known eastern Pacific species of Salmoneus is provided. However, several immature and/or incomplete specimens herein preliminarily reported as Salmoneus spp., as well photographic records from southern California, USA, indicate the presence of further undescribed species in the eastern Pacific.